Permeability of the Anterior Lens Capsule for Large Molecules and Small Drugs. (22nd July 2013) - Kastner, Christian; Löbler, Marian; Sternberg, Katrin; Reske, Thomas; Stachs, Oliver; Guthoff, Rudolf; Schmitz, Klaus-Peter
Abstract: Purpose : For developing injectable lenses the retention properties of the capsular bag are important. Therefore the apparent permeability coefficients of sodium fluorescein and fluorescent dextrans of different sizes were determined for the human anterior lens capsule to calculate a molecular weight cutoff from these data. In addition, permeability coefficients of drugs helpful for the suppression of secondary cataract were determined. Materials and Methods : Capsulorhexis specimens were fixed in a specially designed two compartment diffusion chamber to investigate the permeation of sodium fluorescein and fluorescent dextrans of different sizes (10, 40, 70 and 150 kDa) for 24 h ( n  ≥ 3) and of the antiproliferative drugs actinomycin D and methotrexate for 0.5, 24, 48 and 72 h ( n  ≥ 3). Results : The molecular weight cutoff of the anterior lens capsule was found to be 166 ± 82 kDa. After 0.5 h, no passage of actinomycin D and methotrexate was detectable through the lens capsule. The apparent permeability coefficients for actinomycin D and methotrexate were calculated to 0.71 ± 0.02 µm/s and to 0.80 ± 0.13 µm/s, respectively. Conclusions : The capsular bag retains fluorescent dextrans with a molecular weight of >166 kDa. Hence, prepolymers are required to polymerize rapidly to be retained inside of the capsular bag. In addition, low-molecular substances intended as antiproliferative drugs for secondary cataract prevention should be applied within a time frame of five minutes in such a way that cells adjacent to the capsular bag will not be damaged.